A diatomite-derived N-doped carbon aerogel with 98% sulfur loading for the enhancement of Li–S battery performance. (27th February 2023) - Jiang, Zhiyi; Zhang, Shilin; Dong, Xiongbo; Xu, Zonglin; Sarwar, Muhammad Tariq; Yan, Chenyu; Yang, Caihong; Tang, Aidong; Yang, Huming
Abstract : The ultralight carbon material with diatomite as template can drive 98 wt% sulfur material with only 2 wt%, and it still has high performance when used as the cathode material for lithium sulfur batteries. Abstract : Improving the sulfur content and cycling performance of the cathode is the key to the commercial application of lithium–sulfur batteries. Herein, the diatomite-derived nitrogen-doped carbon aerogel provides an ample sulfur loading space that can be loaded with 98% sublimated sulfur. The Li–S battery delivered an initial discharge capacity of 703.1 mAh g −1 and still retained 510.1 mAh g −1 at 0.5C after 200 cycles, which is attributed to the highly disordered carbon and catalytic activity.